Ethnolinguistic and ethnocultural features of the phenomenon of abbreviation in a language - Ibragimova, Gulchexra (The Lingua Spectrum, 2025)
The article analyzes the essence of the concepts of ethnolinguistics and ethnoculture, the object of study, the views expressed by researchers, and the ethnolinguistic and ethnocultural characteristics of abbreviations that make up the lexical reserve of the language.